Using first bout effect to study the mechanisms underlying eccentric exercise induced force loss - Orawan Prasartwuth (2018)
© 2017 Elsevier Ltd. Introduction: The first bout of eccentric exercise is known to have a protective effect on the consequent bouts. This effect is still disputable as it is not known whether it protects muscle damage by reducing force production or by improving force recovery in the healing process. The underlying mechanisms of this protective effect have not been fully understood. Objectives: To determine the mechanisms of this protective effect, three different loads were used for the first eccentric bout. This was done to investigate whether the protective effect is related to the size of the load in the first bout. To determine the neural adaptations, voluntary activation was assessed and to determine the muscular adaptations, the resting twitch was measured. Method: Thirty healthy participants were selectively allocated into three groups (low-, moderate- and high-load group) to match for maximal voluntary contraction (MVC) (n = 10 per group). Participants in each group performed only one of the three sets of ten eccentric (ECC) exercises of the elbow flexors (10%, 20% and 40% of MVC) as their first eccentric bout. The second bout of eccentric exercise was performed two weeks later and was identical for all the three groups, i.e., 40% ECC. Results: The results showed that for the first bout, MVC, voluntary activation and the resting twitch displayed significant (p < 0.0001) interaction (group x time). This was not the case however for the second bout as there was no significant (group x time) interaction in all outcome variables immediately after exercise. When the first and second bouts were compared, it was found that the high-load group had faster recovery in MVC at day 1 and 4 corresponding to voluntary activation and only at day 4 corresponding to the resting twitch. Conclusions: In this study, it was found that high-load exercise aids fast recovery either via neural or muscular adaptations.